Analysis of the Application of Information and Communication Technology (ICT) in the Islamic Religious Education Learning Process at SMKN 2 Jiwan - Suwartiningsih, Suwartiningsih (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
This study aims to determine the application of Information Technology and Communication in the learning process of Islamic Religious Education which consists of aspects of computer technology, multimedia technology, communication technology and technology computer networks, teacher abilities and skills in using technology Information and Communication inside and outside the classroom in the learning process and the extent to which teachers use Information and Communication Technology as a medium and learning resources for Islamic Religious Education. The research method uses a quantitative descriptive research approach by utilizing a questionnaire and then processing it with statistical validity and reliability tests with a significance level of 5%. Next process The analysis uses a technique approach to the frequency of concentration and size measurement deployment. The results of this study indicate that the teacher has implemented Information and Communication Technology in the learning process of Religious Education Islam at SMK N 2 Jiwan is classified as good with an average score of all three aspects is 70.37%.